THE INFLUENCE OF BUCKWHEAT FLOUR ON THE QUALITY OF THE CONFECTIONERY«VANILLA COOKIES» - VOROBETS, МARIA; DOLISHNYAK, PAVLO (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The work is devoted to the study of the influence of the introduction of buckwheat flour into the recipe of the confectionery product «Vanilla cookies» on its organoleptic and some physicochemical indicators. Wheat flour was replaced with buckwheat in quantity wt. %: 5, 10, 25, 50, 100 at the stage of kneading the dough. Products made according to the traditional recipe of «Vanilla cookies» by the private enterprise "Halochka", which is located in the village of Yabluniv, Kosiv district, Ivano-Frankivsk region selected as a control sample. According to the results of the tasting commission, it was established that the proposed samples with buckwheat flour 5, 10 and 25 wt. % of wheat flour are very close in organoleptic properties to the control sample (without buckwheat flour). Not much worse than the control sample are products with a buckwheat flour content of 50 wt. %. «Vanilla cookies» with 100% buckwheat flour is significantly different. The results of studies of some physicochemical properties (porosity, brittleness) of the proposed samples of «Vanilla cookies» depending on the proportion of wheat flour replaced by buckwheat indicate that the porosity is almost at the level of the control samples. Only for products with a 5% (wt.) replacement of wheat flour with buckwheat, the porosity is 4% lower compared to the control sample. Regarding such an indicator as brittleness, there is a dependence: the more buckwheat flour, the more brittle the products. Samples made only from buckwheat flour are very brittle, they are inconvenient to consume, since they crumble when touched. In general, the conducted studies confirmed the possibility and feasibility of improving the nutritional value of the flour confectionery product «Vanilla cookies» by introducing buckwheat flour into the composition of the composite flour mixture. Formation of qualitative organoleptic and physicochemical properties of the proposed samples of confectionery products «Vanilla cookies» is possible if 10 – 25 % of wheat flour replaced with buckwheat flour.
Keywords: buckwheat flour; wheat flour; confectionery flour products; organoleptic indicators; «Vanilla cookies»